Evaluation of Oxidative Stress Parameters and Genotoxic Effects in Patients With Work-Related Asthma and Silicosis. Issue 2 (8th February 2023) - Kurt, Ozlem Kar; Ergun, Dilek; Anlar, Hatice Gul; Hazar, Merve; Aydin Dilsiz, Sevtap; Karatas, Mevlut; Basaran, Nursen
Abstract : To our knowledge, present study is first to examine oxidative stress and genotoxic parameters in patients with WRA. There is limited number of studies about silicosis. Both parameters were found to be statistically significantly higher in exposure, WRA, silicosis groups. Our study results shed light on mechanisms of two diseases. Abstract : Objective: To determine the mechanistic roles of oxidative stress, inflammation, and genotoxicity parameters in patients with work-related asthma (WRA) and silicosis. Methods: Thirty-eight healthy office workers, 27 employees with a history of exposure and no disease, 24 employees with WRA, and 23 employees with silicosis were included in this study. Superoxide dismutase, catalase, glutathione peroxidase, malondialdehyde, and interleukins (IL) 17, 23, and 27 levels were measured in the serum. Genotoxic damage was evaluated by calculating the frequency of micronuclei in swab samples and 8-hydroxy-2'-deoxyguanosine in serum. Results: Serum superoxide dismutase, catalase, glutathione peroxidase, malondialdehyde, 8-hydroxy-2'-deoxyguanosine, and IL-17, IL-23, and IL-27 levels were found to be statistically significantly higher in the exposure, WRA, and silicosis groups compared with the control group. The frequency of micronuclei in buccal epithelial cells of the patient group was found to be significantly higher than that of the control group. Conclusion: These results may provide information for molecular mechanisms and early diagnosis of WRA and silicosis and will be a guide for taking precautions in the early period.